The effect of exercise on quality of life in postmenopausal women referred to the Bone densitometry centers of Iran University of Medical Sciences - Soghra Nikpour; Hamid Haghani (Wolters Kluwer Medknow Publications, 2014)
Background: One of the most critical stages of women's lives is menopause and one of the aims of health for all in the 21st century is the improvement of the quality of life.Aim and Objective: The aim of this study was to determine the effect of exercise on quality of life in postmenopausal women.Materials and Methods: This study was designed by a randomized-controlled trial. Eighty volunteer postmenopausal women who experienced the menopause period naturally and have been taking hormone replacement treatment (HRT) were divided into two groups randomly (exercise group n = 40, control group n = 40). The Nottingham Health Profile (NHP) was used to assess quality of life in both groups before and after 8 weeks. The exercise group participated in an exercise program, which was composed of sub-maximal aerobic exercises for an 8-week period 5 times a week. Quality of life in two groups was compared at the end of 8 weeks.Results: The results showed that there was a statistically significant difference in the exercise group for the NHP indicating an improvement in the quality of life (P < 0.05).Conclusion: We concluded that quality of life on postmenopausal women could be improved with a regular and controlled exercise program of 8 weeks. Thus, implementing appropriate educational programs to promote the quality of life in postmenopausal women is recommended.